Purification and characterization of peptide deformylase from Helicobacter pylori expressed in Escherichia coli - Thi Thanh Trung, Do; Hong Diep, Le; Bao Yen, Pham (VNU Journal of Science: Natural Sciences and Technology, 2017)
Helicobacter pylori is the major reason causesing gastrointestinal diseases and is characterized with the rapidly increase of multi drug resistance. In this project, we focused on studying peptide deformylase catalyzing for the crucial N-formyl cleavage from N-formyl methionyl at the beginning of new peptide chains in prokaryotes as an alternative target for screening potential anti- H. pylori compounds. The 24.5 kDa recombinant Hp PDF expressed in E. coli BL21-RIL was successfully purified with a 13-fold increase in purity and 37.2% yield. Hp PDF formyl removing pecific activity was determined at 145.3 U/mg with K m of 137.16 µM and k cat / K m ratio of 173.42 M -1 s -1